Psychoeducation of Adolescent Mental Health at SMP P Malang City - Dini Cahyani (Universitas Muhammadiyah Ponorogo, 2023)
SMP P is one of the schools fostered by the Pandanwangi Health Center. Clients are students and teachers at SMP P, totaling 23 people. Based on the results of interview assessments, observations, and the depression, anxiety, and stress scale 42 (DASS 42). Based on the interview results, it is known that students and teachers at SMP P do not have knowledge related to mental health and how to deal with individuals with complaints of being stressed. The results of the DASS 42 scale screening given to 52 class VIII students showed that there were 23 students indicated to be experiencing depression, anxiety, and stress. Psychoeducation is provided in the form of delivery of material, case roleplay, relaxation exercises, discussion, and question and answer accompanied by pre-test and post-test questionnaires to measure client knowledge after and before being given psychoeducation. The purpose of providing this intervention is to increase client knowledge related to mental health in adolescents and mental health promotion. The result of the intervention was an increase in the client's knowledge about mental health before and after the intervention with a significance value of .000 (p 0.05).